The Relationship between the Dimensions of Warmth and Control in Perceived Parenting Style and Peer Pressure on Externalizing Behavior in Middle School Adolescents - Yulia Vicarista Lengu; IGAA Noviekayati; Dyan Evita Santo (Kirana Publisher (KNPub), 2026)
This study analyzes the relationship between the dimensions of warmth and control in perceived parenting style, as well as peer pressure, on externalizing behavior in middle school adolescents. A quantitative correlational design was used, involving a sample of 100 middle school students in Surabaya selected through purposive sampling. The research instruments consisted of an externalizing behavior scale, a perceived parenting style scale, and a peer pressure scale. The results show that the warmth and control dimensions of perceived parenting style have a significant relationship with adolescent externalizing behavior. Additionally, peer pressure was also found to significantly contribute to the emergence of externalizing behavior. These findings affirm the importance of a warm parenting style and proportional parental control, as well as managing peer influence, in preventing externalizing behavior. In conclusion, a combination of positive parenting and healthy social support can be an important predictor for reducing externalizing behavior in adolescents. This research is expected to be a reference for parents, educators, and psychology practitioners in developing appropriate interventions to support the healthy behavioral development of adolescents.